Enhancing PV modules efficiency and power output using multi-concept cooling technique - Linus Idoko; Olimpo Anaya-Lara; Alasdair McDonald (Energy Reports, 2018)
The efficiency and power output of a PV module decrease at the peak of sunlight due to energy loss as heat energyand this reduces the module power output. Multi-concept cooling technique, a concept that involves three types of passive cooling, namely conductive cooling, air passive cooling and water passive cooling has the potential to tackle this challenge. The experiment was set up using two solar panels of 250 watts each with both modules mounted at a height of 37~cm to create room for air-cooling, with the application of water-cooling at the surface of one of the PV modules to reduce the surface temperature to 2̊0 C. The rear of the same module attached to an aluminium, Al heat sink. The other module also mounted was without water-cooling and Al heat sink attachment. The Al heat sink comprises aluminium plate attached with aluminium fins to aid cooling, and water at a reduced temperature achieved with the introduction blocks of ice facilitated the module surface cooling. Analysis of the power output achieved, carried out with the help of the equation for PV array power output with a derating factor of 80%. The experiment recorded an increase in output power of 20.96 watts, and an increase in efficiency of not less than 3% achieved thus making the module more efficient and productive.
Keywords: 330; Cooling; Efficiency improvement; Module temperature; PV power output